Fatal Plasmodium falciparum, Clostridium perfringens, and Candida spp. Coinfections in a Traveler to Haiti - Gillian L. Genrich; Julu Bhatnagar; Christopher D. Paddock; Sherif R. Zaki (Journal of Tropical Medicine)
Malaria is one of the most common causes of febrile illness in travelers. Coinfections with bacterial, viral, and fungal pathogens may not be suspected unless a patient fails to respond to malaria treatment. Using novel immunohistochemical and molecular techniques, Plasmodium falciparum, Clostridium perfringens, and Candida spp. coinfections were confirmed in a German traveler to Haiti. Plasmodium falciparum-induced ischemia may have increased this patient's susceptibility to C. perfringens and disseminated candidiasis leading to his death. When a patient presents with P. falciparum and shock and is unresponsive to malaria treatment, secondary infections should be suspected to initiate appropriate treatment.